Analysis the Dimension of CSR Towards the Relationship Between Psychological Contract and Knowledge Sharing - Tiara Puspa; Noval Juan Wijaya (Universitas Pasundan, 2018)
This research aims to analyze the dimension of corporate social responsibility (consisting of legal and economic) and its relationship to psychological contract, as well as the psychological contract that has relation to knowledge sharing. The object of this sample is employee’s PT Television Transformation Indonesia (Trans TV) in Jakarta. To test the hypotheses, this study distributed 265 surveys. Among these, 10 surveys were excluded because of incomplete responses. A total of 255 surveys were Analyzed by using the method of Structural Equation Model (SEM). The result shows that legal CSR and Economic CSR has no relation with psychological contract, but the psychological contract has significantly, the positive relation to knowledge sharing. Further research can take another sample from the different media industry.